2024
DOI: 10.1021/acsami.3c16115
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Nature’s Bath Sponge into Stacking Faults-Enhanced Ag Nanorings-Decorated Catalyst for Hydrogen Evolution Reaction

Chirag R. Ratwani,
Shadeepa Karunarathne,
Ali Reza Kamali
et al.

Abstract: The rational design of cost-effective and efficient electrocatalysts for electrochemical water splitting is essential for green hydrogen production. Utilizing nanocatalysts with abundant active sites, high surface area, and deliberate stacking faults is a promising approach for enhancing catalytic efficiency. In this study, we report a simple strategy to synthesize a highly efficient electrocatalyst for the hydrogen evolution reaction (HER) using carbonized luffa cylindrica as a conductive N-doped carbon skele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…It was found that Au, Ag, Cu and other metal clusters with inert H 2 evolution also display unique electrocatalytic H 2 production activity. 40–42 These metal elements feature relatively cheap prices and high earth reserves, making the study of non-platinum metal electrocatalysis even more valuable for HER.…”
Section: Electrocatalytic H2 Productionmentioning
confidence: 99%
“…It was found that Au, Ag, Cu and other metal clusters with inert H 2 evolution also display unique electrocatalytic H 2 production activity. 40–42 These metal elements feature relatively cheap prices and high earth reserves, making the study of non-platinum metal electrocatalysis even more valuable for HER.…”
Section: Electrocatalytic H2 Productionmentioning
confidence: 99%
“…Noble metals remain at the top of the list of high-performing catalysts. 9,10 However, excessive costs limit the practical usage of noble metals and their derivatives in LABs. 11 Numerous low-cost alternatives have shown promising results, such as doped/undoped carbon 12 and derivatives of non-precious transition metals, including their oxides, 13 and sulfides.…”
Section: Introductionmentioning
confidence: 99%